2006
DOI: 10.1136/adc.2005.073262
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of an early neurofunctional assessment in predicting neurodevelopmental outcome in very low birthweight infants

Abstract: Early neurofunctional evaluation may be useful in predicting later neurodevelopmental outcome in VLBW children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 29 publications
3
18
2
1
Order By: Relevance
“…Picciolini et al reported that neurobehavioural evaluations in early infancy, such as the BRS, may be useful for predicting the neurodevelopmental outcome in VLBW children [33].…”
Section: Discussionmentioning
confidence: 99%
“…Picciolini et al reported that neurobehavioural evaluations in early infancy, such as the BRS, may be useful for predicting the neurodevelopmental outcome in VLBW children [33].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple methods are available, such as the Amiel-Tison neurological examination, 1 the Touwen Infant Neurological Examination (TINE), 2 the Hammersmith Infant Neurological Examination (HINE), 3 and the neurofunctional assessment of Picciolini et al 4 Little is known about the reliability of these widely used methods. 5 The validity of neurological assessments has been studied to some extent; marked neurological dysfunction during infancy has considerable power to predict developmental disability such as cerebral palsy (CP).…”
Section: Discussionmentioning
confidence: 99%
“…25 Our study confirmed the relationship between preterm birth and MND in infancy. 4,25,26 Signs of MND may be an expression of the lesions of the developing brain associated with preterm birth, such as focal and diffuse damage of the periventricular white matter, and lesions of the thalamus, basal ganglia, and cerebellum. 25,27 Interestingly, we found that small-for-gestational age and preeclampsia were protective factors in the development of MND in the second half of infancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of early assessment at the time of development means that we are not only able to act at an early stage, but also to apply preventive and optimization measures in order to obtain lasting benefits, since what occurs in early infancy has a lasting effect on cognitive capacity, personality, and social behavior (McCormick et al, 2006;Picciolini, Giannì, Vegni, Fumagalli, & Mosca, 2006;Poch et al, 2003;Sonnander, 2000;Stanton-Chapman, Chapman, Bainbridge, & Scott, 2002).…”
Section: Discussionmentioning
confidence: 99%